Low-temperature cured polyurethane varnish resin for automobiles and preparation method of low-temperature cured polyurethane varnish resin

Through the synergistic effect of the double cross-linking system, bismuth complex-blocked curing agent and modified fiber, the problem of short service life of low-temperature curing varnish is solved, rapid curing at 65°C and the formation of a high-performance varnish layer are achieved, bubble defects are avoided, and it is suitable for automotive polyurethane varnish.

CN120718528AActive Publication Date: 2025-09-30HUATU CHEM (JILIN) CO LTD

Patent Information

Application Number
CN202511204838.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-27
Publication Date
2025-09-30
Estimated Expiration
2045-08-27

AI Technical Summary

Technical Problem

The low-temperature curing of traditional automotive polyurethane varnishes results in a short shelf life, which cannot balance the needs of shelf life and low-temperature curing. In addition, high-temperature baking is not friendly to heat-sensitive substrates, resulting in varnish waste.

Method used

A double-crosslinking system and a bismuth complex-enclosed curing agent and modified fiber synergistic system are adopted. The reaction activity of the resin matrix and the curing agent is reduced through the physical barrier of the fiber and the active dormancy of the bismuth complex. Poly(decane-4,6-diynedioic acid) is used to quickly decomplex at 65°C, combined with a bismuth neodecanoate catalyst to catalyze the cross-linking reaction, forming a network interpenetrating structure, extending the service life and avoiding bubble defects.

Benefits of technology

It achieves rapid curing at around 65°C, prolongs the shelf life of the mixture of resin and curing agent, ensures the varnish is stably stored at room temperature, and reacts quickly after spraying to form a high-performance varnish layer, avoiding bubbles and pinhole defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120718528A_ABST
    Figure CN120718528A_ABST
Patent Text Reader

Abstract

The invention discloses a low-temperature cured polyurethane varnish resin for automobiles and a preparation method thereof, and belongs to the technical field of chemical product processing, the low-temperature cured polyurethane varnish resin comprises a resin matrix and a curing agent, the resin matrix comprises a component A and a component B. The component A comprises a crosslinking system A1, a crosslinking system A2 and an auxiliary agent, the component B is a curing activity regulator of a double-crosslinking system of the crosslinking system A1 and the crosslinking system A2; the curing agent is diethyl malonate blocked isocyanate; the cross-linking system A1 is mainly composed of hydroxy acrylic resin containing beta-diketone metal ligand and a bismuth neodecanoate catalyst; the bismuth neodecanoate catalyst and a beta-diketone metal ligand form a bismuth complex; the cross-linking system A2 is mainly composed of hydroxyl acrylic resin containing alkoxy silane groups; the component B is prepared from poly (decane-4, 6-diyne diacid) modified nano porous fibers and a silane coupling agent. The service life of the varnish is prolonged on the basis of ensuring low-temperature rapid curing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical product processing and relates to a low-temperature solidified polyurethane varnish resin for automobiles and a preparation method thereof. Background Art

[0002] Traditional automotive polyurethane varnishes usually need to be baked and cured at temperatures of 120-140°C or even higher, which is not friendly to heat-sensitive substrates, and high-temperature baking will accelerate the aging of metal substrates. Therefore, a large number of low-temperature curing varnishes have appeared. Low-temperature curing of varnish means that the resin matrix and curing agent have high reactivity after mixing. As a result, after the resin matrix and curing agent are mixed and diluted into varnish, it must be used up in a short time, generally within 2-3 hours (such as 9900 super varnish). Because the resin matrix and curing agent will produce a continuous curing reaction after mixing, as time goes by, the degree of curing continues to increase. When it increases to a certain extent, the performance indicators of the varnish no longer meet the usage standards. The short service life leads to a large amount of varnish waste. Summary of the Invention

[0003] The purpose of the present invention is to provide a low-temperature curing polyurethane varnish resin for automobiles and a preparation method thereof, which solves the problem that the current low-temperature curing varnish has a short service life and cannot balance the service life with low-temperature curing.

[0004] The technical solution adopted in the present invention is as follows: A low-temperature curing polyurethane varnish resin for automobiles, comprising a resin matrix and a curing agent. The resin matrix comprises component A and component B, wherein component A comprises a crosslinking system A1, a crosslinking system A2, and an auxiliary agent, and component B is a curing activity regulator for a dual crosslinking system of crosslinking systems A1 and A2. The curing agent is a diethyl malonate blocked isocyanate. The cross-linking system A1 is mainly composed of a hydroxy acrylic resin containing a β-diketone metal ligand and a bismuth neodecanoate catalyst; the bismuth neodecanoate catalyst forms a bismuth complex with the β-diketone metal ligand; The cross-linking system A2 is mainly composed of a hydroxy acrylic resin containing an alkoxysilane group; The component B includes poly (decane-4,6-diynedioic acid) modified nanoporous fibers and a silane coupling agent.

[0005] The present invention achieves rapid curing of the resin at around 65°C by utilizing a dual cross-linking system and a bismuth neodecanoate catalyst-isocyanate catalytic curing system. The low-temperature curing in this application mainly refers to a curing temperature below 100°C rather than the traditional low temperature (e.g., 10°C or below). Due to rapid curing at low temperatures, the resin and curing agent have a shelf life of 2-3 hours after mixing. The resin must be completely used within 2-3 hours; after that, it cannot be used normally. To extend this shelf life, the present invention introduces a bismuth complex-blocked curing agent and modified fiber synergistic system. This system utilizes the physical barrier of the fiber and the active dormancy of the bismuth complex-blocked curing agent to reduce contact between the resin matrix and the curing agent and lower their reactivity. The synergistic effect significantly extends the shelf life of the resin and curing agent after mixing at room temperature. The decomplexation temperature of the bismuth complex is generally greater than 65°C. In the prior art, the bismuth complex cannot be quickly decomplexed at a curing temperature of about 65°C, making it difficult to achieve low-temperature rapid curing of the polyurethane varnish. Therefore, while extending the room-temperature service life of the varnish obtained by mixing the resin matrix and the curing agent, in order to achieve low-temperature rapid curing during curing (returning to the above-mentioned low-temperature rapid curing requirement), the present invention introduces poly(decane-4,6-diynedioic acid). Poly(decane-4,6-diynedioic acid) will produce succinic acid in light and air. Succinic acid promotes the rapid decomplexation of the bismuth metal complex at about 65°C, releasing bismuth ions and reforming the neodecanoate catalyst. When poly(decane-4,6-diynedioic acid) produces succinic acid, it will also produce CO2. CO2 causes the varnish layer to have bubbles, pinholes, and other phenomena. In order to avoid solving this problem, the present invention uses fiber as a carrier of poly(decane-4,6-diynedioic acid). The fiber structure forms a built-in exhaust channel, which effectively avoids defects such as bubbles or pinholes in the cured paint film caused by CO2 retention. The bismuth neodecanoate catalyst catalyzes the deblocking of diethyl malonate blocked isocyanate, releasing -NCO, which undergoes a cross-linking and curing reaction with the hydroxy acrylic resin. Simultaneously, the bismuth neodecanoate catalyst also catalyzes a cross-linking reaction of a dual cross-linking system (cross-linking systems A1 and A2). During the cross-linking process of the cross-linking systems A1 and A2, a network interpenetrating structure is formed. This interpenetrating structure can improve the performance of the varnish. In addition, the modified fiber can also enhance the performance of the varnish. Therefore, the present invention can prepare a high-performance polyurethane varnish.

[0006] In summary, after the curing agent of the present invention is mixed and diluted with a resin matrix to form a varnish, it is stable when stored in the dark, the reaction activity between the resin matrix and the curing agent-bismuth catalyst is low, and the service life is long. When the varnish is sprayed, the reaction activity between the resin matrix and the curing agent-bismuth catalyst can be rapidly increased under air (oxygen), light, and heating conditions, achieving low-temperature rapid curing, and obtaining a high-performance varnish layer.

[0007] Furthermore, the crosslinking system A1 comprises the following components in parts by weight: 90-110 parts of a hydroxy acrylic resin containing a β-diketone metal ligand, 20-25 parts of propylene glycol methyl ether acetate, and 1.8-2.5 parts of a bismuth neodecanoate catalyst; the bismuth neodecanoate catalyst forms a bismuth complex with the β-diketone metal ligand; The crosslinking system A2 comprises the following components in parts by weight: 90-110 parts of a hydroxy acrylic resin containing an alkoxysilane group, 1-1.2 parts of a hindered amine light stabilizer, and 0.8-1.2 parts of a silane hydrolysis inhibitor.

[0008] Furthermore, the mass ratio of component A to component B is 100:6-8.

[0009] Furthermore, the mass ratio of the poly (decane-4,6-diynedioic acid) modified nanoporous fiber to the silane coupling agent in the component B is 5-7:1; The poly (decane-4,6-diynedioic acid) modified nanoporous fiber is prepared by the following method: A. Dissolving cellulose acetate in a mixed solvent of acetone and dimethylacetamide in a mass ratio of 8:2 to prepare a spinning solution; subjecting the spinning solution to an electrospinning process to obtain a porous fiber membrane; immersing the porous fiber membrane in a 0.1 M NaOH ethanol solution for hydrolysis, washing with water, and drying for later use; B. In the absence of oxygen, in the dark, disperse poly(decane-4,6-diynedioic acid) microparticles, PEG-PPG block copolymer, and potassium perfluorooctane sulfonate in deionized water and ultrasonically treat to obtain a suspension; C. Under anaerobic dark conditions, the reserved porous fiber membrane was immersed in the suspension, vacuum infiltrated and freeze-dried, and then immersed in an acetone solution containing 1-chloro-4-propoxythioxanthone, filtered, dried and sheared to obtain poly (decane 4,6-diynedioic acid) modified nanoporous fibers.

[0010] Furthermore, the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane KH-560 or γ-aminopropyltriethoxysilane KH-550.

[0011] Furthermore, the hindered amine light stabilizer is light stabilizer UV-292 or light stabilizer XH-622LD; and the silane hydrolysis inhibitor is 1,3-divinyltetramethyldisiloxane.

[0012] Furthermore, the auxiliary agent includes a defoaming agent, a leveling agent, and a dispersant.

[0013] A method for preparing a low-temperature curing polyurethane varnish resin for automobiles comprises the following steps: S1. Preparation of component A S1.1. Preparation of crosslinking system A1: In a light-proof reactor, add a hydroxy acrylic resin containing a β-diketone metal ligand and propylene glycol methyl ether acetate in proportion, stir and disperse evenly at 25-30°C, then add a bismuth neodecanoate catalyst, and heat to 50-60°C to react and form a bismuth complex to obtain crosslinking system A1; S1.2. Preparation of crosslinking system A2: Under dry nitrogen protection, add a hydroxyl acrylic resin containing an alkoxysilane group in proportion, add a hindered amine light stabilizer and a silane hydrolysis inhibitor while stirring, and react at 40-45°C for 20-30 minutes to obtain crosslinking system A2; S1.3, Mixing crosslinking system: Mix crosslinking systems A1 and A2 at 35-40°C, continue stirring until uniform, add auxiliary agent, and stir for 30-40 minutes to obtain component A; S2. preparing component B: uniformly mixing the poly(decane-4,6-diynedioic acid) modified nanoporous fibers and the silane coupling agent to obtain component B; S3. Add component B to component A under high-speed stirring, mix well to obtain a resin matrix, and seal the resin matrix and the curing agent separately and store the resin matrix in a vacuum and away from light.

[0014] Furthermore, the hydroxy acrylic resin containing β-diketone metal ligands is prepared by the following method: acetylacetone and glycidyl methacrylate in a mass ratio of 1:1 are reacted at 60-65°C with triethylamine as a catalyst to obtain an intermediate monomer, and then the intermediate monomer is reacted with hydroxyethyl acrylate, methyl methacrylate, butyl acrylate, and styrene under the action of an initiator for heating to obtain the hydroxy acrylic resin containing β-diketone metal ligands.

[0015] Furthermore, the hydroxy acrylic resin containing alkoxy silane groups is prepared by the following method: γ-methacryloxypropyltrimethoxysilane, hydroxyethyl acrylate, methyl methacrylate, butyl acrylate, and styrene are heated to react under the action of an initiator to obtain the hydroxy acrylic resin containing alkoxy silane groups.

[0016] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. The present invention discloses a low-temperature curing polyurethane clearcoat resin for automobiles. After the curing agent and resin matrix are mixed and diluted to form a clearcoat, the clearcoat is stable when stored in the dark. The reactivity between the resin matrix and the curing agent-bismuth catalyst is low, resulting in a long shelf life. After the clearcoat is sprayed, the reactivity between the resin matrix and the curing agent-bismuth catalyst is rapidly enhanced under conditions of air (oxygen), light, and heating, achieving rapid low-temperature curing and producing a high-performance clearcoat layer. 2. The present invention achieves rapid curing of the resin at around 65°C by utilizing a dual cross-linking system and a bismuth neodecanoate catalyst-isocyanate catalytic curing system; 3. The poly(4,6-decanediol)-modified nanoporous fibers of the present invention not only rapidly enhance the reactivity between the resin matrix and the curing agent, but also form built-in exhaust channels to prevent the gas generated by the poly(4,6-decanediol) from affecting the quality of the varnish layer. 4. The present invention introduces a bismuth complex-blocked curing agent and modified fiber synergistic system, utilizing the physical barrier of the fiber and the active dormancy of the bismuth complex-blocked curing agent to reduce the contact between the resin matrix and the curing agent and lower the reaction activity of the resin matrix and the curing agent. The two synergistically significantly extend the service life of the mixed resin and curing agent at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be considered as limiting the scope. A person of ordinary skill in the art can also derive other relevant drawings based on these drawings without inventive effort, among which: Figure 1 This is a process flow chart for preparing the low-temperature curing polyurethane varnish resin for automobiles of the present invention; Figure 2-Figure 3 This is a physical picture of the low-temperature curing polyurethane varnish resin for automobiles used as a varnish. DETAILED DESCRIPTION

[0018] In order to make the objectives, technical solutions, and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only intended to explain the present invention and are not intended to limit the present invention. That is, the embodiments described herein are only some embodiments of the present invention, not all embodiments. Generally, the components of the embodiments of the present invention described and illustrated in the drawings herein may be arranged and designed in various different configurations.

[0019] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention as claimed, but is merely intended to represent selected embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative work are within the scope of protection of the present invention.

[0020] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus comprising a series of elements includes not only those elements, but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus. In the absence of further limitations, an element defined by the phrase "comprising a ..." does not exclude the presence of additional identical elements in the process, method, article, or apparatus comprising the element.

[0021] The features and performance of the present invention are further described in detail below with reference to the embodiments.

[0022] Example 1: A preferred embodiment of the present invention provides a low-temperature curing polyurethane varnish resin for automobiles, comprising a resin matrix and a curing agent. The resin matrix comprises component A and component B. Component A comprises a crosslinking system A1, a crosslinking system A2, and an auxiliary agent. Component B is a curing activity regulator for a dual crosslinking system of crosslinking systems A1 and A2. The curing agent is a diethyl malonate blocked isocyanate. The crosslinking system A1 comprises the following components in parts by weight: 90 parts of a hydroxy acrylic resin containing a β-diketone metal ligand, 20 parts of propylene glycol methyl ether acetate, and 1.8 parts of a bismuth neodecanoate catalyst; the bismuth neodecanoate catalyst forms a bismuth complex with the β-diketone metal ligand; The crosslinking system A2 comprises the following components in parts by weight: 90 parts of a hydroxyl acrylic resin containing an alkoxysilane group, 1 part of a hindered amine light stabilizer, and 0.8 parts of a silane hydrolysis inhibitor; the hindered amine light stabilizer is light stabilizer UV-292 or light stabilizer XH-622LD, and in this embodiment, light stabilizer UV-292 is selected; the silane hydrolysis inhibitor is 1,3-divinyltetramethyldisiloxane; The component B includes poly (decane-4,6-diynedioic acid) modified nanoporous fibers and a silane coupling agent.

[0023] The mass ratio of component A to component B is 100:6.

[0024] The mass ratio of the poly (decane-4,6-diynedioic acid) modified nanoporous fibers to the silane coupling agent in component B is preferably 6:1. The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane KH-560 or γ-aminopropyltriethoxysilane KH-550. In this embodiment, γ-glycidyloxypropyltrimethoxysilane KH-560 is selected. The poly (decane-4,6-diynedioic acid) modified nanoporous fiber is prepared by the following method: A. Dissolving cellulose acetate in a mixed solvent of acetone and dimethylacetamide at a mass ratio of 8:2 to prepare a spinning solution; subjecting the spinning solution to an electrospinning process to obtain a porous fiber membrane; immersing the porous fiber membrane in a 0.1 M NaOH ethanol solution for hydrolysis, washing with water, and drying for later use; B. In the absence of oxygen, in the dark, poly(decane-4,6-diynedioic acid) microparticles, PEG-PPG block copolymer (the mass ratio of PEG to PPG in the PEG-PPG block copolymer is 3:1), and potassium perfluorooctane sulfonate were dispersed in deionized water and sonicated to obtain a suspension; C. Under anaerobic dark conditions, the reserved porous fiber membrane was immersed in the suspension, vacuum infiltrated and freeze-dried, and then immersed in an acetone solution containing 1-chloro-4-propoxythioxanthone, filtered, dried and sheared to obtain poly (decane 4,6-diynedioic acid) modified nanoporous fibers.

[0025] The additives include defoamers, leveling agents, and dispersants. The amount of additives used is dynamically adjusted based on the amount used in the prior art and the actual situation. like Figure 1 As shown, a method for preparing a low-temperature curing polyurethane varnish resin for automobiles comprises the following steps: S1. Preparation of component A S1.1. Preparation of crosslinking system A1: In a light-proof reactor, add a hydroxy acrylic resin containing a β-diketone metal ligand and propylene glycol methyl ether acetate in proportion, stir and disperse evenly at 25-30°C, then add a bismuth neodecanoate catalyst, and heat to 50-60°C to react and form a bismuth complex to obtain crosslinking system A1; S1.2. Preparation of crosslinking system A2: Under dry nitrogen protection, add a hydroxyl acrylic resin containing an alkoxysilane group in proportion, add a hindered amine light stabilizer and a silane hydrolysis inhibitor while stirring, and react at 40-45°C for 20-30 minutes to obtain crosslinking system A2; S1.3, Mixing crosslinking system: Mix crosslinking systems A1 and A2 at 35-40°C, continue stirring until uniform, add auxiliary agent, and stir for 30-40 minutes to obtain component A; S2. preparing component B: uniformly mixing the poly(decane-4,6-diynedioic acid) modified nanoporous fibers and the silane coupling agent to obtain component B; S3. Add component B to component A under high-speed stirring, mix well to obtain a resin matrix, and seal the resin matrix and the curing agent separately and store the resin matrix in a vacuum and away from light.

[0026] The hydroxy acrylic resin containing β-diketone metal ligands is prepared by the following method: acetylacetone and glycidyl methacrylate in a mass ratio of 1:1 are reacted at 60-65°C with triethylamine as a catalyst to obtain an intermediate monomer, and then the intermediate monomer is heated with hydroxyethyl acrylate, methyl methacrylate, butyl acrylate, and styrene under the action of an initiator to react to obtain the hydroxy acrylic resin containing β-diketone metal ligands; wherein the mass ratio of the intermediate monomer to hydroxyethyl acrylate, methyl methacrylate, butyl acrylate, and styrene is: 1:2:3:2:1.

[0027] The hydroxy acrylic resin containing an alkoxysilane group is prepared by the following method: γ-methacryloxypropyltrimethoxysilane, hydroxyethyl acrylate, methyl methacrylate, butyl acrylate, and styrene are heated to react under the action of an initiator to obtain a hydroxy acrylic resin containing an alkoxysilane group; wherein the mass ratio of γ-methacryloxypropyltrimethoxysilane, hydroxyethyl acrylate, methyl methacrylate, butyl acrylate, and styrene is 8:25:30:20:8.

[0028] Example 2: This example is based on Example 1, but differs from Example 1 in that: the crosslinking system A1 includes the following components in parts by weight: 100 parts of a hydroxy acrylic resin containing a β-diketone metal ligand, 23 parts of propylene glycol methyl ether acetate, and 2.3 parts of a bismuth neodecanoate catalyst; the bismuth neodecanoate catalyst forms a bismuth complex with the β-diketone metal ligand; The crosslinking system A2 comprises the following components in parts by weight: 100 parts of a hydroxy acrylic resin containing an alkoxysilane group, 1.1 parts of a hindered amine light stabilizer, and 1 part of a silane hydrolysis inhibitor. The remaining components are the same.

[0029] Example 3: This example is based on Example 1, but differs from Example 1 in that: the crosslinking system A1 comprises the following components in parts by weight: 110 parts of a hydroxy acrylic resin containing a β-diketone metal ligand, 25 parts of propylene glycol methyl ether acetate, and 2.5 parts of a bismuth neodecanoate catalyst; the bismuth neodecanoate catalyst forms a bismuth complex with the β-diketone metal ligand; The crosslinking system A2 comprises the following components in parts by weight: 110 parts of a hydroxy acrylic resin containing an alkoxysilane group, 1.2 parts of a hindered amine light stabilizer, and 1.2 parts of a silane hydrolysis inhibitor. The remaining components are the same.

[0030] Example 4: This example is based on Example 2, but differs from Example 2 in that the mass ratio of component A to component B is 100:7. The rest of the contents are the same.

[0031] Example 5: This example is based on Example 2, but differs from Example 2 in that the mass ratio of component A to component B is 100:8. The rest of the contents are the same.

[0032] Comparative Example 1: Based on Example 1, this comparative example is different from Example 1 in that it does not contain cross-linking system A1. The resin matrix is ​​prepared with cross-linking system A2, auxiliary agent, and component B as the main components, and the remaining parts are adaptively adjusted.

[0033] Comparative Example 2: Based on Example 1, this comparative example is different from Example 1 in that it does not contain cross-linking system A2. The resin matrix is ​​prepared with cross-linking system A1, auxiliary agent, and component B as the main components, and the remaining parts are adaptively adjusted on the basis of Example 1.

[0034] Comparative Example 3: Based on Example 1, this comparative example is different from Example 1 in that the cross-linking system A1 in this comparative example is mainly composed of hydroxy acrylic resin and bismuth neodecanoate catalyst, the hydroxy acrylic resin does not contain β-diketone metal ligand, the cross-linking system A1 contains bismuth neodecanoate catalyst, and no bismuth complex is formed. The remaining parts are adaptively adjusted on the basis of Example 1.

[0035] Comparative Example 4: Based on Example 1, this comparative example differs from Example 1 in that the crosslinking system A2 in this comparative example does not contain a hindered amine light stabilizer, and the remaining parts are adaptively adjusted based on Example 1.

[0036] Comparative Example 5: Based on Example 1, this comparative example differs from Example 1 in that the crosslinking system A2 in this comparative example does not contain a silane hydrolysis inhibitor, and the remaining parts are adaptively adjusted based on Example 1.

[0037] Comparative Example 6: Based on Example 1, this comparative example is different from Example 1 in that it does not contain a curing agent, and the remaining parts are adaptively adjusted on the basis of Example 1.

[0038] Comparative Example 7: Based on Example 1, this comparative example is different from Example 1 in that the curing agent in this comparative example is an unblocked isocyanate curing agent, and the remaining parts are adaptively adjusted on the basis of Example 1.

[0039] Comparative Example 8: Based on Example 1, this comparative example is different from Example 1 in that it does not contain component B, and the remaining parts are adaptively adjusted on the basis of Example 1.

[0040] Comparative Example 9: Based on Example 1, this comparative example differs from Example 1 in that component B in this comparative example only includes poly(decane-4,6-diynedioic acid), and the remaining components are adaptively adjusted based on Example 1.

[0041] Comparative Example 10: Based on Example 1, this comparative example differs from Example 1 in that component B in this comparative example is only nanoporous fibers and silane coupling agent, and does not contain poly (decane-4,6-diynedioic acid), and the remaining parts are adaptively adjusted based on Example 1.

[0042] Comparative Example 11: Based on Example 1, this comparative example is different from Example 1 in that component B in this comparative example does not contain a silane coupling agent.

[0043] Test Example 1: The resin matrix in Examples 1-5 and Comparative Examples 1-11 was diluted and mixed with a curing agent to prepare an automotive varnish. The apparent characteristics of the varnish before and after curing and its service life in the dark at room temperature were tested. The results are shown in Table 1.

[0044] The surface characteristics of the varnish before and after curing include visible color, transparency, and the presence of precipitation; Shelf life at room temperature: Take samples every half hour and test the viscosity according to the coating viscosity determination method (GB / T 1723-1993); End of shelf life: viscosity > 50s or gelation, precipitation, turbidity and other abnormalities appear.

[0045] Table 1 Varnish test results

[0046] The blocked isocyanate curing agent, bismuth complex, and fiber barrier in the present invention can all delay resin cross-linking and extend the service life. The release of isocyanate and bismuth catalysts seriously affects the curing speed and paint layer quality. The longer the curing time, the greater the environmental impact on the paint layer and the worse the quality. The release of isocyanate and bismuth catalysts will be affected by component B. Therefore, component B in the present invention is very important, affecting not only the curing speed but also the quality of the paint layer.

[0047] Test Example 2: Based on Test Example 1, the curing time of the varnish in Test Example 1 under air, 65°C, and white light irradiation and the varnish layer performance with no abnormalities in the macroscopic characteristics after curing were tested. The test results are shown in Table 2.

[0048] Curing time: Determine the surface dry time and through dry time according to GB / T 1728-2020 "Determination of drying time of paint and putty films"; Adhesion testing: Testing the adhesion performance of varnish according to GB / T 9286-2021, and determining the proportion of peeling area on a scale of 0-5, providing a unified testing basis for quality control in the coatings industry; Weather resistance: After curing, the varnish layer samples were placed in a UV accelerated aging tester for 2000 hours to observe whether there were any abnormal phenomena, such as cracks, powdering, and falling off; after curing, the varnish layer samples were placed in a xenon lamp aging box for 2000 hours to observe whether there were any abnormal phenomena; if there were no abnormalities, it was confirmed that the weather resistance was good; Gasoline resistance: After curing, varnish layer test pieces are immersed in 90# gasoline at room temperature for 48 hours to observe whether there are any abnormalities, including whitening, blistering, paint peeling, wrinkling, cracking, rusting, obvious loss of gloss, softening of coating, etc. Hardness test: Test the hardness of the varnish layer according to GB / T 6739-2022 “Paints and varnishes - Determination of film hardness by pencil method”.

[0049] Table 2 Varnish performance test results

[0050] The invention has a short curing time and good hardness, weather resistance, gasoline resistance and adhesion.

[0051] Test Example 3: For the actual application of a certain plate, the varnish prepared in the range of Example 4 is used in combination with black paint, as shown in the actual picture. Figure 2 、 3 As shown, Figure 2 It is the color paint layer without clear varnish spraying. Figure 3 The varnish is a colored paint layer for spraying varnish, and the varnish of the present invention does not affect the black color development but can also improve the glossiness.

[0052] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions and improvements made by any technician familiar with the field within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A low-temperature curing polyurethane varnish resin for automobiles, characterized in that: The invention comprises a resin matrix and a curing agent, wherein the resin matrix comprises component A and component B, wherein component A comprises a crosslinking system A1, a crosslinking system A2, and an auxiliary agent, and component B is a curing activity regulator of a dual crosslinking system of crosslinking system A1 and crosslinking system A2; and the curing agent is a diethyl malonate blocked isocyanate. The cross-linking system A1 is mainly composed of a hydroxy acrylic resin containing a β-diketone metal ligand and a bismuth neodecanoate catalyst; the bismuth neodecanoate catalyst forms a bismuth complex with the β-diketone metal ligand; The cross-linking system A2 is mainly composed of a hydroxy acrylic resin containing an alkoxysilane group; The component B includes poly (decane-4,6-diynedioic acid) modified nanoporous fibers and a silane coupling agent.

2. The low-temperature curing polyurethane varnish resin for automobiles according to claim 1, characterized in that: The crosslinking system A1 comprises the following components in parts by weight: 90-110 parts of a hydroxy acrylic resin containing a β-diketone metal ligand, 20-25 parts of propylene glycol methyl ether acetate, and 1.8-2.5 parts of a bismuth neodecanoate catalyst; the bismuth neodecanoate catalyst forms a bismuth complex with the β-diketone metal ligand; The crosslinking system A2 comprises the following components in parts by weight: 90-110 parts of a hydroxy acrylic resin containing an alkoxysilane group, 1-1.2 parts of a hindered amine light stabilizer, and 0.8-1.2 parts of a silane hydrolysis inhibitor.

3. The low-temperature curing polyurethane varnish resin for automobiles according to claim 1, characterized in that: The mass ratio of component A to component B is 100:6-8.

4. The low-temperature curing polyurethane varnish resin for automobiles according to claim 1, characterized in that: The mass ratio of the poly (decane-4,6-diynedioic acid) modified nanoporous fiber and the silane coupling agent in the component B is 5-7:1; The poly (decane-4,6-diynedioic acid) modified nanoporous fiber is prepared by the following method: A. Dissolving cellulose acetate in a mixed solvent of acetone and dimethylacetamide in a mass ratio of 8:2 to prepare a spinning solution; subjecting the spinning solution to an electrospinning process to obtain a porous fiber membrane; immersing the porous fiber membrane in a 0.1 M NaOH ethanol solution for hydrolysis, washing with water, and drying for later use; B. In the absence of oxygen, in the dark, disperse poly(decane-4,6-diynedioic acid) microparticles, PEG-PPG block copolymer, and potassium perfluorooctane sulfonate in deionized water and ultrasonically treat to obtain a suspension; C. Under anaerobic dark conditions, the reserved porous fiber membrane was immersed in the suspension, vacuum infiltrated and freeze-dried, and then immersed in an acetone solution containing 1-chloro-4-propoxythioxanthone, filtered, dried and sheared to obtain poly (decane 4,6-diynedioic acid) modified nanoporous fibers.

5. The low-temperature curing polyurethane varnish resin for automobiles according to claim 4, characterized in that: The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane KH-560 or γ-aminopropyltriethoxysilane KH-550.

6. The low-temperature curing polyurethane varnish resin for automobiles according to claim 2, characterized in that: The hindered amine light stabilizer is light stabilizer UV-292 or light stabilizer XH-622LD; the silane hydrolysis inhibitor is 1,3-divinyltetramethyldisiloxane.

7. The low-temperature curing polyurethane varnish resin for automobiles according to claim 1, characterized in that: The auxiliary agents include defoaming agents, leveling agents and dispersants.

8. The method for preparing a low-temperature curing polyurethane varnish resin for automobiles according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Preparation of component A S1.

1. Preparation of crosslinking system A1: In a light-proof reactor, add a hydroxy acrylic resin containing a β-diketone metal ligand and propylene glycol methyl ether acetate in proportion, stir and disperse evenly at 25-30°C, then add a bismuth neodecanoate catalyst, and heat to 50-60°C to react and form a bismuth complex to obtain crosslinking system A1; S1.

2. Preparation of crosslinking system A2: Under dry nitrogen protection, add a hydroxyl acrylic resin containing an alkoxysilane group in proportion, add a hindered amine light stabilizer and a silane hydrolysis inhibitor while stirring, and react at 40-45°C for 20-30 minutes to obtain crosslinking system A2; S1.3, Mixing crosslinking system: Mix crosslinking systems A1 and A2 at 35-40°C, continue stirring until evenly mixed, then add the additive and stir for 30-40 minutes to obtain component A; S2. preparing component B: uniformly mixing the poly(decane-4,6-diynedioic acid) modified nanoporous fibers and the silane coupling agent to obtain component B; S3. Add component B to component A under high-speed stirring, mix well to obtain a resin matrix, and seal the resin matrix and the curing agent separately and store the resin matrix in a vacuum and away from light.

9. The method for preparing a low-temperature curing polyurethane varnish resin for automobiles according to claim 8, characterized in that: The hydroxy acrylic resin containing β-diketone metal ligands is prepared by the following method: acetylacetone and glycidyl methacrylate in a mass ratio of 1:1 are reacted at 60-65°C with triethylamine as a catalyst to obtain an intermediate monomer; the intermediate monomer is then heated to react with hydroxyethyl acrylate, methyl methacrylate, butyl acrylate, and styrene under the action of an initiator to obtain the hydroxy acrylic resin containing β-diketone metal ligands.

10. The method for preparing a low-temperature curing polyurethane varnish resin for automobiles according to claim 8, characterized in that: The hydroxy acrylic resin containing alkoxysilane groups is prepared by the following method: γ-methacryloxypropyltrimethoxysilane, hydroxyethyl acrylate, methyl methacrylate, butyl acrylate, and styrene are heated and reacted under the action of an initiator to obtain the hydroxy acrylic resin containing alkoxysilane groups.

Citation Information

Patent Citations

  • Electrocoating compositions with amine ligands

    CN102264954A

  • Nylon nanofiber three-dimensional cross-linking macroporous bracket and preparation method thereof

    CN105749339A

  • Moisture-curing compositions

    CN111479628A

  • Super-flat seam beautifying agent and seam leveling construction process thereof

    CN118638500A

  • Initiator system and adhesive composition made therewith

    CN1201467A

Cited By

  • Process for preparing rare earth modified pearl paint for automobiles and application of rare earth modified pearl paint

    CN122326118A